PERAN MAHKAMAH KONSTITUSI DALAM MEWUJUDKAN FAIR EQUALITY OF OPPORTUNITY DI INDONESIA (ANALISIS PUTUSAN NOMOR 117/PUU-VII/2009) - Wicaksono, Dian Agung (Mahkamah Konstitusi Republik Indonesia, 2012)
Through the decision No. 117/PUU-VII/2009, Constitutional Court applies Rawls conception of justice that emphasizes the equality of all people with equality of opportunity by applying fair or equal opportunity principle. Institutional design between the DPR and DPD viewed by Constitutional Court as an inequiality condition, so that to reach a value of justice, equal opportunity principle should take precedence and priority. Stregthening DPD is necessary to uphold the checks and balances mechanisms in Indonesia.